Clinical utility of the FilmArray® meningitis/encephalitis panel in children with suspected central nervous system infection in a low-resource setting – a prospective study in Southwestern Uganda - Reza Rasti; Elias Kumbakumba; Deborah Nanjebe; Phuthumani Mlotshwa; Milly Nassejje; John Mzee; Stephen Businge; Gilbert Akankwasa; Dan Nyehangane; Jesper Gantelius; Yap Boum; Andreas Mårtensson; et al. (BMC Infectious Diseases)
Abstract Background In low-resource settings, limited laboratory capacity adds to the burden of central nervous system (CNS) infections in children and spurs overuse of antibiotics. The commercially available BioFire® FilmArray® Meningitis/Encephalitis Panel (FA-ME) with its capability to simultaneously detect 14 pathogens in cerebrospinal fluid (CSF), could potentially narrow such a diagnostic gap. Methods In Mbarara, Uganda, we compared clinical utility (clinical turnaround time [cTAT], microbial yield, and influence on patient outcome and antibiotic exposure) of FA-ME with bacterial culture, in children 0–12 years with suspected CNS infection. Results Of 212 enrolled children, CSF was sampled from 194. All samples underwent bacterial culture, of which 193 also underwent FA-ME analyses. FA-ME analyses prospectively influenced care for 169 of the 193 patients, and they constituted an ‘Index group’. The remaining 43/212 patients constituted a ‘Reference group’. Of all 194 CSF-sampled patients, 87% (168) had received antibiotics before lumbar puncture. Median cTAT for FA-ME was 4.2 h, vs. two days for culture. Bacterial yield was 12% (24/193) and 1.5% (3/194) for FA-ME and culture, respectively. FA-ME viral yield was 12% (23/193). Fatality rate was 14% in the Index group vs. 19% in the Reference group (P = 0.20). From clinician receival of FA-ME results, median antibiotic exposure was 6 days for bacteria-negative vs. 13 days for bacteria-positive patients (P = 0.03). Median hospitalization duration was 7 vs. 12 days for FA-ME negative and positive patients, respectively (P < 0.01). Conclusions In this setting, clinical FA-ME utility was found in a higher and faster microbial yield and shortened hospitalization and antibiotic exposure of patients without CSF pathology. More epidemiologically customized pathogen panels may increase FA-ME utility locally, although its use in similar settings would require major cost reductions. Trial registration The trial was registered with clinicaltrials.gov (NCT03900091) in March 2019, and its protocol was published in November 2020.